Analysis of an Automated Control System for Air Conditioner Temperature In Industrial Production Rooms Using a Fuzzy Logic Method Based on Production Load and Environmental Temperature Detection - Arya Pratama; Solly Aryza; Hamdani (CERED Indonesia Institute, 2025)
Temperature control in industrial production rooms is a crucial factor in maintaining product quality stability and work comfort. This study aims to analyze the temperature control automation system in Air Conditioners (AC) using the Fuzzy Logic method integrated with production load and environmental temperature detection. This system is designed to automatically adjust the AC cooling performance based on variations in production intensity and actual temperature conditions in the factory environment. Input data in the form of production load and environmental temperature are processed using fuzzy logic rules to determine the optimal cooling output level. Test results show that the system is able to respond to parameter changes in real-time and maintain the production room temperature within the predetermined ideal range. The application of this method improves energy efficiency and extends the operational life of the AC compared to conventional control systems. Thus, the fuzzy logic approach based on load and environmental temperature is proven effective as an adaptive solution in temperature control automation systems in industrial environments.